Associations of Stress Exposures and Social Support With Long-Term Mental Health Outcomes Among U.S. Iraq War Veterans. Issue 5 (September 2018) - Ciarleglio, Maria M.; Aslan, Mihaela; Proctor, Susan P.; Concato, John; Ko, John; Kaiser, Anica Pless; Vasterling, Jennifer J.
Abstract: The long-term mental health effects of war-zone deployment in the Iraq and Afghanistan wars on military personnel are a significant public health concern. Using data collected prospectively at three distinct assessments during 2003–2014 as part of the Neurocognition Deployment Health Study and VA Cooperative Studies Program Study #566, we explored how stress exposures prior, during, and after return from deployment influence the long-term mental health outcomes of posttraumatic stress disorder (PTSD), depression, anxiety disorders, and problem drinking. Longer-term mental health outcomes were assessed in 375 service members and military veterans an average of 7.5 years (standard deviation = 1.0 year) after the initial (i.e., "index") Iraq deployment following their predeployment assessment. Anxiety disorder was the most commonly observed long-term mental health outcome (36.0%), followed by depression (24.5%), PTSD (24.3%), and problem drinking (21.0%). Multivariable regression models showed that greater postdeployment stressors, as measured by the Post-Deployment Life Events scale, were associated with greater risk of depression, anxiety disorders, and problem drinking. Anxiety disorder was the only outcome affected by predeployment stress concerns. In addition, greater postdeployment social support was associated with lower risk of all outcomes except problem drinking. These findings highlight the importance of assessing postdeployment stress exposures, such as stressful or traumatic life events, given the potential impact of these stressors on long-term mental health outcomes. This study also highlights the importance of postdeployment social support as a modifiable protective factor that can be used to help mitigate risk of long-term adverse mental health outcomes following war-zone exposure. Highlights: Prospective study of stress and long-term mental health outcomes in warzone veterans. Examined impact of predeployment, deployment, and postdeployment stress exposures. Postdeployment stressors linked to mental disorders and increased symptom severity. Predeployment stressors were associated with anxiety symptoms and disorders. Postdeployment social support associated with reduced risk of mental disorders.